Restoration of soil quality of degraded grassland can be accelerated by reseeding in an arid area of Northwest China - Lu, Qi; Ma, Hongbin; Zhou, Yao; Liu, Jindi; Shen, Yan (Frontiers in Plant Science, 2023)
Grassland restoration measures control soil degradation and improve soil quality (SQ) worldwide, but there is little knowledge about the effectiveness of restoration measures affecting SQ in arid areas, and the restoration rate of degraded grasslands to natural restoration grasslands and reseeded grasslands remains unclear. To establish a soil quality index (SQI) to evaluate the effects of different grassland restoration measures on SQ, continuous grazing grassland (CG) (as a reference), grazing exclusion grassland (EX), and reseeding grassland (RS) were selected and sampled in the arid desert steppe. We conducted using two soil indicator selection methods (Total data set, TDS, and Minimum data set, MDS), followed by three SQ indices (Additive soil quality index, SQIa; Weighted additive soil quality index, SQIw; Nemoro soil quality index, SQIn). The results indicated that SQ was better assessed using the SQIw (R2 = 0.55) compared to SQIa and SQIn for indication differences among the treatments due to the larger coefficient of variance. The SQIw-MDS value in CG grassland was 46% and 68% lower than EX grassland and RS grassland, respectively. Our findings provided evidence that restoration practices of grazing exclusion and reseeding can significantly improve the SQ in the arid desert steppe, and native plant reseeded can accelerate soil quality restoration.